Combination of high on-treatment platelet aggregation and low deaggregation better predicts long-term cardiovascular events in PCI patients under dual antiplatelet therapy. (September 2014) - Müller, K. A. L.; Karathanos, A.; Tavlaki, E.; Stimpfle, F.; Meissner, M.; Bigalke, B.; Stellos, K.; Schwab, M.; Schaeffeler, E.; Müller, I. I.; Gawaz, M.; Geisler, T.
Abstract High on-treatment platelet reactivity is associated with short-term major cardiovascular (CV) events in patients undergoing percutaneous coronary intervention (PCI). Maximum and final aggregation assessed by light transmission aggregometry (LTA) have both been used to predict short-term outcome after PCI, however their long-term prognostic impact remains controversial. There is currently no information regarding the prognostic role of deaggregation and its added value in combination with established aggregation parameters. About 1279 patients with symptomatic coronary artery disease (CAD) undergoing PCI were enrolled in this monocentric study. On-treatment platelet aggregation under clopidogrel maintenance therapy, as well as deaggregation was determined by maximum and final aggregation (5 min after adding of the agonist). Deaggregation was defined as slope of the tangent between Aggmax +0.5 min. Primary endpoints were the composite of myocardial infarction, stroke, and CV death or stent thrombosis according to the ARC criteria. Low deaggregation, defined as values in the lowest tertile (<1.5), was more frequent in patients with acute coronary syndromes (ACS) compared to patients with stable angina pectoris (SAP), ACS: 29.6% vs. SAP: 22.0%, p = 0.001. The combination of high on-treatment platelet reactivity, defined by the upper tertile of Aggmax and low deaggregation, was associated with significantly increased risk for combined long-term CV events. The combination of low deaggregation and high on-treatment platelet reactivity is associated with higher risk for recurrent events in patients with CAD undergoing PCI. Thus, deaggregation might be a more sensitive parameter providing added value in terms of risk prediction for long-term recurrent CV events in relation with established aggregation parameters.